2010
DOI: 10.1515/bc.2010.146
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of haptoglobin glycoform variants in psoriasis

Abstract: Haptoglobin is an acute phase glycoprotein, secreted by hepatocytes and other types of cells including keratinocytes. Haptoglobin has been suggested to impair the immune response, inhibit gelatinases in the extracellular matrix and promote angiogenesis, but its role in psoriasis is obscure to date. Changes in haptoglobin glycan structure were observed in several diseases. The aim of this study was to investigate whether haptoglobin displays glycan variations in psoriasis. We found that the pattern of plasma ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Our study found that decreased protein expression of serum Hp-b in combination with increased Lewis X-type fucosylation could be a promising diagnostic marker for LC detection. Increase in Hp Lewis X-type fucosylation has been suggested to impair the immune response, inhibit gelatinases in the extracellular matrix, promote angiogenesis, and may give an advantage to the tumor [8]. These findings also suggest that this marker could be employed in a course-monitoring strategy for the clinical management of patients with liver diseases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study found that decreased protein expression of serum Hp-b in combination with increased Lewis X-type fucosylation could be a promising diagnostic marker for LC detection. Increase in Hp Lewis X-type fucosylation has been suggested to impair the immune response, inhibit gelatinases in the extracellular matrix, promote angiogenesis, and may give an advantage to the tumor [8]. These findings also suggest that this marker could be employed in a course-monitoring strategy for the clinical management of patients with liver diseases.…”
Section: Discussionmentioning
confidence: 93%
“…Besides, changes in the Hp glycan structure are observed in several other diseases. Sarrats et al [5] have detected increased levels of Sialyl-Lewis X (SLe(x)) on Hp in chronic pancreatitis, and Maresca et al [8] have found that the level of distinct fucosylated glycoforms is higher in psoriasis patients than in healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The structural modification of Hp in psoriasis patients is an abundance or structure change of specific glycans that differ or do not exist in Hp from healthy donors. These changes are associated with altered function of that might have an impact on the disease activity (Maresca et al, 2010). Interestingly, it was found that there is no higher prevalence of any of the three phenotypes of Hp in psoriasis.…”
Section: Psoriasismentioning
confidence: 95%
“…2D-GE was performed according to Maresca et al [18], with each sample run in duplicate. For the first-dimension of electrophoresis, 200 lg of plasma protein samples (approximately 3 ll) were applied to 18-cm linear IPG strips 4-7 (GE Healthcare, Uppsala, Sweden) and focused until 72,000 V/h were reached.…”
Section: Methodsmentioning
confidence: 99%